Expert System Identifikasi Penyakit Dan Hama Tanaman Manggis Menggunakan Algoritma Certainty Factor - Iqbal Mahadi; Adi Prijuna Lubis; Afdhal Syafnur (LPPM STMIK Royal Kisaran, 2022)
Abstract: Mangosteen is a tropical fruit that is widely cultivated in Indonesia. In general, many are honed who cultivate mangosteen fruit, but farmers still experience problems in dealing with pests and diseases of mangosteen, to overcome the existing problems, the agricultural extension helps to understand farmers to identify these pests and diseases. The Asahan District Agriculture Office in identifying mangosteen diseases is still done manually because in the limited time mangosteen farmers cannot receive training from unscheduled farmer counseling. So to make it easier to understand in identifying diseases, researchers create an expert system that can build to identify diseases and pests in mangosteen in percentage probability, using a certainty factor algorithm for the application of an effective expert system in overcoming the problem. The accuracy in the calculation process of the certainty factor algorithm is influenced by the selection of the data for the existing symptoms. Keywords: diseases and pests; mangosteen plants; expert systems; certainty factor. Abstrak: Buah manggis merupakan buah tropis yang banyak dibudidayakan di Indonesia . pada umumnya diasahan banyak yang membudiadayakan buah manggis, namun petani masih mengalami kendala dalam menagani hama dan penyakit manggis, untuk mengatasi permasalahan permasalahan yang ada, penyuluhan pertanian membantu untuk melakukan pemahaman kepada petani agar dapat mengidentifikasi hama dan penyakit tersebut. Adapun Dinas Pertanian Kabupaten Asahan dalam melakukan identifikasi penyakit manggis masih secara manual, karena dalam keterbatasan waktu petani manggis tidak dapat pelatihan dari penyuluhan petani yang tidak terjadwalkan. Maka untuk mempermudah dalam memahami dalam mengidentifikasi penyakit peneliti membuat sistem pakar yang dapat membangun untuk mengidentifikasi penyakit dan hama pada manggis dalam probabilitas persentasenya, menggunakan algoritma certainty factor untuk penerapan sistem pakar ekfektif dalam mengatasi permasalahannya. Keakuratan dalam proses perhitungan algoritma certainty factor yang dipengaruhi oleh pemilihan data gejala-gejala yang ada. Kata kunci: penyakit dan hama; tanaman manggis; sistem pakar; certainty factor.